2015
DOI: 10.17496/kmer.2015.17.3.110
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the Successful Design and Implementation of Competency‐Based Medical Education in Korea

Abstract: Competency-based medical education (CBME) is an outcome-oriented curriculum model for medical education that organizes learning activities and assessment methods according to defined competencies as the learning outcomes of a given curriculum. CBME emerged to address the accountability of medical education in response to growing concerns about thepatient safety in North America in the 1970s, and the number of medical schools adopting CBME has dramatically increased since 1990. In Korea, CBME has been under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…CBE is the process of designing classes, developing instructional materials for students and instructors, operating curricula, and assessing students' performance based on the students' outcomes using an objective structured system. 16,18) Nevertheless, during the process, the faculty members in charge 2,10,19) have encountered various barriers in operating the curriculum, such as selecting and training virtual patients, in ensuring the validity 1,17) and objectivity of the assessment, and in establishing integrated competency assessment 2,16) due to the lack of individuals with integrated clinical experience who can observe and assess the students' performance. Moreover, faculty members in charge have difficulties in ensuring the education time for developing faculty assessors, time for developing assessment materials, time for teaching students, and time for re-education of students who do not meet the assessment criteria, 18) hence, the implementation of CBA may require more time, effort, and cost compared with traditional paper examinations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CBE is the process of designing classes, developing instructional materials for students and instructors, operating curricula, and assessing students' performance based on the students' outcomes using an objective structured system. 16,18) Nevertheless, during the process, the faculty members in charge 2,10,19) have encountered various barriers in operating the curriculum, such as selecting and training virtual patients, in ensuring the validity 1,17) and objectivity of the assessment, and in establishing integrated competency assessment 2,16) due to the lack of individuals with integrated clinical experience who can observe and assess the students' performance. Moreover, faculty members in charge have difficulties in ensuring the education time for developing faculty assessors, time for developing assessment materials, time for teaching students, and time for re-education of students who do not meet the assessment criteria, 18) hence, the implementation of CBA may require more time, effort, and cost compared with traditional paper examinations.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the requirement of developing competencybased education (CBE) for improving the graduation competency and academic outcomes, CBE using a competency assessment has already been implemented in most domestic medical schools, allowing students to perform in a realistic practice setting. [1][2] However, pharmacy schools have not implemented a systematic approach to prepare all students to achieve their goals or outcomes in Korea. Although the Korean Association of Pharmacy Education (KAPE) has been discussing about reforming the curriculum of pharmacy schools through public hearings on competency-based, outcome-based pharmacy education 3) and has established major areas of essential competencies, no assessment tools have been developed for faculty members to measure the outcomes of established competencies and for pharmacy students to easily understand and successfully access the assessment test.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study also suggested that professors should improve their teaching methods further to enhance medical education, including competency training and evaluation. 22 As such, professors who want to use smartphone-based training should first improve their expertise. Furthermore, in order to increase students' acceptance of and adaptability to new, unfamiliar teaching methods, previous education on the use of smartphones and platforms, such as Google Classroom, and preparation of schema diagrams is necessary.…”
Section: Discussionmentioning
confidence: 99%